CBD (Cannabidiol) Product Attitudes, Knowledge, and Use Among Young Adults. (15th April 2020) - Wheeler, Meghann; Merten, Julie Williams; Gordon, Benjamin T; Hamadi, Hanadi
Abstract: Background: Cannabidiol (CBD), a non-psychoactive component of cannabis is marketed as a potential treatment for many conditions and widely available to purchase as a dietary supplement. In 2017, sales of CBD exceeded 820 million dollars despite many unconfirmed health claims, murky legality, and limited product efficacy and safety testing. Purpose/Objectives: This study aims to explore cannabidiol (CBD) knowledge, attitudes, and use among young adults. Methods : The anonymous 36-item survey developed using Qualtrics was distributed via social media from November 2018 to January 2019 with 340 respondents. Results: Of the 340 respondents, 242 reported they had heard of CBD, and 135 reported using CBD products. CBD users were primarily white, female, without children, made less than $25, 000 per year, and unmarried. Most commonly used CBD products were edibles (56.30%), tinctures (54.07%), and vape (38.52%). Top reasons for use included stress relief (65.39%), relaxation (54.81%), and sleep improvement (42.22%). Many respondents reported using guesswork to determine dosage, and over half of respondents reported at least one unanticipated side effect. Conclusions/Importance: This study revealed that many users are not responsibly using CBD products, many believe CBD products provide health benefits that are not yet scientifically proven, and they are not knowledgeable about legal and regulatory issues. Until CBD use is more thoroughly researched and has more comprehensive regulation, public health professionals should address alternative stress and anxiety treatment methods.